Industrialization Lessons from BRICS: A Comparative Analysis - Wim A. Naudé; Adam Szirmai; Alejandro Lavopa (Institute for the Study of Labor (IZA), 2013)
To date there has been few systematic and comparative empirical analyses of the nature of economic development in Brazil, Russia, India, China and South Africa (BRICS). We contribute to addressing this gap by exploring the patterns of structural change between 1980 and 2010, focusing on the manufacturing sector. We show that three of the BRICS are experiencing de-industrialization (Brazil, Russia and South Africa). China is the only country where an expanding manufacturing sector accounts for a significant part of aggregate growth. We explore the differences in patterns and causes of manufacturing between China and the other BRICS. These differences are down to differences in industrial policy: in China industrial policy supported both foreign and domestic investment for technological catch-up. It is the only country where FDI favoured the manufacturing sector and manufactured exports, and where domestic investment started becoming increasingly important compared to FDI from 1995 onward.
Keywords: F23; L52; L53; O25; O40; O33; O34; 330; foreign direct investment; multinational enterprises; industrialization; technology; innovation; entrepreneurship; Brazil; Russia; China; India; South Africa